Chitosan-promoted sepiolite supported Ag as efficient catalyst for catalytic oxidative degradation of formaldehyde at low temperature. Issue 6 (December 2022) - Li, Dongdong; Liu, Pingle; Zheng, Yiru; Wu, Yi; Ling, Le; Chen, Liting; Hao, Fang; Lv, Yang; Xiong, Wei; Luo, He'an
Abstract: The chitosan (CTs) modified high purity sepiolite (HP-Sep) supported Ag nanoparticles catalyst (CTs-Ag/HP-Sep) was prepared by impregnation and applied in the catalytic oxidation of HCHO. 5CTs-10Ag/HP-Sep-300 (5 and 10 represent the weight percentage of 5% chitosan and 10% Ag, and 300 represents the calcination temperature of 300 °C) with abundant amino and hydroxyl groups, smaller highly dispersed metallic Ag nanoparticles presented superior adsorbability of HCHO and better oxidative degradation performance. The 100 ppm HCHO under the GHSV of 6000 mL/g·h can be completely oxidized to H2O and CO2 at low temperature of 52 °C. The addition of CTs was conducive to the HCHO adsorption, the formation of smaller Ag nanoparticles with lattice oxygen and the transformation of formate into carbonate species, hence promoting the HCHO oxidative degradation. The possible reaction route was discussed in detail based on the results of XPS and in-situ DRIFTS. This study will provide a promising way for designing highly efficient heterogeneous catalysts by combining nature clay with polymers supported active metal for the oxidative degradation of HCHO at low temperature. Graphical Abstract: ga1 Highlights: Low cost sepiolite presents good adsorbability and used as the catalyst support. CTs promotes HCHO adsorption and lead to smaller highly dispersed metallic Ag. CTs helps to transform formate into carbonate so as to promote HCHO degradation. CTs-Ag/HP-Sep presented good adsorbability and oxidative degradation performance.